Comments to the paper "A nonlinear dynamic uniaxial strength criterion that considers the ultimate dynamic strength of concrete" by Dechun Lu, Guosheng Wang, Xiuli Du, Yang Wang. Int J Impact Eng 103 (2017), 124–137. (November 2017) - Xu, H; Wen, H.M.
Highlights: Equation (6) is completely the same as Eq. (27) of Ref. [1]. Some incorrect statement/description of Ref.[1] needs to be corrected.. The non-linear dynamic uniaxial compressive strength criterion of [1] has not differentiated the dynamic compressive strength due to strain rate effect only from that ascribed to inertia effect only.